2008
DOI: 10.1007/s12231-008-9043-6
|View full text |Cite
|
Sign up to set email alerts
|

Wild Mushroom Markets in Central Mexico and a Case Study at Ozumba

Abstract: Wild Mushroom Markets in Central Mexico and a Case Study at Ozumba. More than 200 species of wild edible mushrooms are consumed in Mexico, and over 100 are sold in local, regional, and wholesale markets. This paper analyzes general trends in the commercialization of wild edible mushrooms at twelve markets in central Mexico, where at least 90 species are sold and more than 100 local names were registered. The paper then focuses its analysis on the traditional market at Ozumba (state of Mexico) near Izta-Popo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
1
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 5 publications
1
62
1
15
Order By: Relevance
“…Apparently, baskets made of natural fibres are still widely used for harvest and selling by local people in Madagascar and Mexico (Montoya et al 2001, Antonín et al 2005, Pérez-Moreno et al 2008, contrary to the observed in our study.…”
contrasting
confidence: 90%
See 2 more Smart Citations
“…Apparently, baskets made of natural fibres are still widely used for harvest and selling by local people in Madagascar and Mexico (Montoya et al 2001, Antonín et al 2005, Pérez-Moreno et al 2008, contrary to the observed in our study.…”
contrasting
confidence: 90%
“…(Montoya et al 2001, Pérez-Moreno et al 2008. Gymnopus dryophilus is known by the vernacular name 'paraguitas' (small umbrellas) and 'popotitos' (skinny people) (Montoya et al 2001) and also 'orejitas' (small ears) due to the cartilaginous consistency of the basidiomata (Pérez-Moreno et al 2008). On the other hand, the Ecuadorian Kichwa's vernacular name for G. nubicola ('kallamba') is not related to any object or part of human body, but means only mushroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La recolección tiene un alto sentido familiar y comunitario (McLain & Jones, 2005;Villarreal-Ruiz & Castillo, 1996), cuya perspectiva de género no ha sido debidamente investigada, pues las mujeres poseen un vasto conocimiento sobre la taxonomía, biología y ecología local de los hongos (Garibay-Orijel, Ramírez-Terrazo, & Ordaz-Velázquez, 2012) y se encuentran involucradas en la recolección, procesamiento, particularmente, en la comercialización (Pérez-Moreno, Martínez-Reyes, Yescas-Pérez, Delgado-Alvarado, & Xoconostle-Cázares, 2008). Asimismo, son ellas las que fomentan el intercambio de información (Montoya et al, 2008) que se mantiene activo de manera vertical (de padres a hijos) y horizontal (entre gente de la misma generación) (Mariaca et al, 2001), conformando parte de su identidad cultural (Garibay-Orijel et al, 2012) y contribuyendo al mantenimiento de los conocimientos ancestrales (Pérez-Moreno et al, 2008). La recolección de hongos ha demostrado ser compatible con la conservación de los recursos naturales a largo plazo (Toledo, 1992), al lograr una producción continua de los bienes y servicios que el bosque proporciona (Villarreal-Ruiz & Pérez-Moreno, 1989), conformando así un componente ecológico.…”
Section: Introductionunclassified
“…Mushroom harvesting has a high family and community sense (McLain & Jones, 2005;Villarreal-Ruiz & Castillo, 1996), the gender aspect of which has not been duly researched, since women have a vast knowledge of the taxonomy, biology and local ecology of mushrooms (Garibay-Orijel, Ramírez-Terrazo, & Ordaz-Velázquez, 2012) and are involved in their gathering, processing and, particularly, marketing (Pérez-Moreno, Martínez-Reyes, Yescas-Pérez, Delgado-Alvarado, & Xoconostle-Cázares, 2008). They are also the ones that foster the exchange of information (Montoya et al, 2008) that is kept active vertically (from parents to children) and horizontally (among people of the same generation) (Mariaca et al, 2001), forming part of their cultural identity (Garibay-Orijel et al, 2012) and contributing to the maintenance of ancestral knowledge (Pérez-Moreno et al, 2008). Mushroom harvesting has proved to be compatible with long-term conservation of natural resources (Toledo, 1992) by achieving a continuous production of goods and services that the forest provides (Villarreal-Ruiz & Pérez-Moreno, 1989), thus forming an ecological component.…”
Section: Introductionmentioning
confidence: 99%